Subjective and objective voice outcomes after transoral laser microsurgery for early glottic cancer. (24th November 2015) - Fink, Daniel S.; Sibley, Haley; Kunduk, Melda; Schexnaildre, Mell; Kakade, Anagha; Sutton, Collin; McWhorter, Andrew J.
Abstract : Objectives/Hypothesis: Transoral laser microsurgery (TLM) continues to gain popularity as a treatment modality for early glottic cancer. Oncologic outcomes have been well‐defined, but there are little data to date describing functional outcomes accounting for stage of resection. Study Design: Retrospective review. Methods: We retrospectively reviewed patient‐rated voice handicap and observer‐rated vocal quality of patients who underwent TLM for early glottic carcinoma. Patients were grouped by European Laryngological Society (ELS) resection type, and the data were combined for ELS type I–III and compared with advanced resections (ELS IV–VI). The Voice Handicap Index (VHI) was used for patient‐rated voice outcomes, and voice recordings were graded by two senior speech‐language pathologists. Voice recordings and VHI scores were taken preoperatively and at least 1 month postoperatively. Results: No major complications were encountered. Six of 49 patients underwent repeat resection for suspicious findings with pathology, demonstrating moderate dysplasia in two cases, carcinoma in situ in two cases, and inflamed mucosa only in two cases. There was no significant difference in preoperative VHI scores or objective voice grades among patients who underwent limited (ELS I–III) and those who required more advanced (ELS IV–VI) resection. There was a significant improvement in VHI scores in patients after ELS type I to III resection, from 38.77 to 22.86 ( P  = .006). There was no significant difference between mean preoperative and postoperative perceptual evaluation scores in patients who underwent ELS type I, II, or III resections (62.25 and 64.32 respectively, P  = .621). Conclusions: Patients who undergo limited ELS resections can be assured of having a similar to improved voice after healing. Patients who undergo extended resections have poorer vocal outcomes. Level of Evidence: 4 Laryngoscope, 126:405–407, 2016